Epidemiology of Norovirus Infection Among Immunocompromised Patients at a Tertiary Care Research Hospital, 2010–2013. (8th September 2016) - Bok, Karin; Prevots, D. Rebecca; Binder, Alison M.; Parra, Gabriel I.; Strollo, Sara; Fahle, Gary A.; Behrle-Yardley, Allison; Johnson, Jordan A.; Levenson, Eric A.; Sosnovtsev, Stanislav V.; Holland, Steven M.; Palmore, Tara N.; et al.
Abstract: Background.  Noroviruses are a major cause of infectious gastroenteritis worldwide, and viruses can establish persistent infection in immunocompromised individuals. Risk factors and transmission in this population are not fully understood. Methods.  From 2010 through 2013, we conducted a retrospective review among immunocompromised patients (n = 268) enrolled in research studies at the National Institutes of Health Clinical Center and identified a subset of norovirus-positive patients (n = 18) who provided stool specimens for norovirus genotyping analysis. Results.  Norovirus genome was identified by reverse-transcription quantitative polymerase chain reaction in stools of 35 (13%) of the 268 immunocompromised patients tested, and infection prevalence was 21% (11 of 53) in persons with primary immune deficiencies and 12% (20 of 166) among persons with solid tumors or hematologic malignancies. Among 18 patients with norovirus genotyping information, norovirus GII.4 was the most prevalent genotype (14 of 18, 78%). Persistent norovirus infection (≥6 months) was documented in 8 of 18 (44%) individuals. Phylogenetic analysis of the GII.4 capsid protein sequences identified at least 5 now-displaced GII.4 variant lineages, with no evidence of their nosocomial transmission in the Clinical Center. Conclusions.  Norovirus was a leading enteric pathogen identified in this immunocompromised population. Both acute and chronic norovirus infections were observed, and these were likely community-acquired. Continued investigation will further define the role of noroviruses in these patients and inform efforts toward prevention and treatment.